Dimeric BODIPYs with different linkages: A systematic investigation on structure-properties relationship. Issue 49 (7th December 2017) - Wang, De-Gao; Zhang, Lin-Na; Li, Qian; Yang, Yuxin; Wu, Yongquan; Fan, Xing; Song, Min; Kuang, Gui-Chao
Abstract: Six dimeric BODIPYsBDP-n (n = 1, 2, 3, 4, 5 and 6) with different linkages were synthesized and their photophysical and electrochemical properties, cell imaging and singlet oxygen generation abilities were studied. The linkages between the two BODIPY units had profound impact on dimeric BODIPYs' fluorescence intensities. The improvement of electron donating ability of the linkage between the two BODIPY units resulted in improved fluorescence intensities. Cell imaging tests indicated dimeric BODIPYs had good biocompatibility with MCF-7 cells. The BODIPY dimers (exceptBDP-5 ) show strong fluorescence in MCF-7 Cells. In addition, bandgap and the fluorescence intensities were the two main factors which influenced the singlet oxygen generation ability. A larger bandgap lead to stronger singlet oxygen generation abilities. We believe that combined well cell imaging and singlet oxygen generation ability endows dimeric BODIPYs a promising perspective in the field of photodynamic therapy. Graphical abstract: